2005
DOI: 10.1038/nm1267
|View full text |Cite
|
Sign up to set email alerts
|

A crucial role of angiotensin converting enzyme 2 (ACE2) in SARS coronavirus–induced lung injury

Abstract: During several months of 2003, a newly identified illness termed severe acute respiratory syndrome (SARS) spread rapidly through the world. A new coronavirus (SARS-CoV) was identified as the SARS pathogen, which triggered severe pneumonia and acute, often lethal, lung failure. Moreover, among infected individuals influenza such as the Spanish flu and the emergence of new respiratory disease viruses have caused high lethality resulting from acute lung failure. In cell lines, angiotensin-converting enzyme 2 (ACE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

79
3,817
5
107

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,347 publications
(4,008 citation statements)
references
References 29 publications
79
3,817
5
107
Order By: Relevance
“…59 Expression at the membrane is downregulated after extracellular shedding by the ADAMs family of zinc metalloproteinases, 60 and by binding of the SARS coronavirus. 61,62 The crucial role of ACE2 in the RAS relies on its ability to cleave Ang I and Ang II to Ang (1-9) and Ang (1-7), respectively ( Fig. 2A).…”
mentioning
confidence: 99%
“…59 Expression at the membrane is downregulated after extracellular shedding by the ADAMs family of zinc metalloproteinases, 60 and by binding of the SARS coronavirus. 61,62 The crucial role of ACE2 in the RAS relies on its ability to cleave Ang I and Ang II to Ang (1-9) and Ang (1-7), respectively ( Fig. 2A).…”
mentioning
confidence: 99%
“…A number of animal models have been used to study the pathogenesis of SARS-CoV infection. Although the monkey model mimics to certain degree the clinical course of SARS (16), the mouse model provides the first genetic evidence for angiotensinconverting enzyme 2 (ACE-2) as a crucial SARS-CoV receptor in vivo (17). Although type-1 pneumocytes, and to a lesser extent type-2 pneumocytes, have been shown to be the target cells of SARS-CoV infection in monkey studies (16,18), the identity of mouse bronchiolar epithelial cells infected by SARS-CoV remains unclear (19,20).…”
mentioning
confidence: 99%
“…Importantly, the increase in lung injury mediated by the Spike protein could be prevented by treating the mice with the ARB losartan. 27 Imai et al 28 extended these studies to investigate other forms of acute respiratory distress syndrome triggered by sepsis and found very similar results: lung injury (as measured by pulmonary edema, leukocyte infiltration, and increased lung elastance) was worsened in ACE2 knockout mice, whereas combined ACE and ACE2 knockout reduced the degree of lung injury to that seen in control animals. In addition, they showed that the severity of lung injury was decreased in Ang II AT 1 knockout mice and increased in AT 2 knockout mice as compared with control animals.…”
Section: Physiological Correlates To Some Interesting Biochemistrymentioning
confidence: 87%
“…27 Infection with the SARS virus leads to severe pneumonia and frequently to respiratory failure. Kuba et al 27 showed that SARS surface Spike protein binds to ACE2 and causes its downregulation.…”
Section: Physiological Correlates To Some Interesting Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation